Pengaruh Multi Leaf Collimator (MLC) Terhadap Besar Dosis Yang Diterima Bagian Kepala Pasien Kanker Otak - Huki, Pascalia Agno Marina; Sutapa, Gusti Ngurah; Sudarsana, I Wayan Balik (Universitas Hamzanwadi, 2023)
Research has been conducted on the effect of Multi Leaf Collimator (MLC) on the dose received by the head of brain cancer patients at Sanglah Hospital, Denpasar. This analysis aims to determine the effect of using MLC on dosing to brain cancer patients using Cobalt 60 (Co-60) teletheraphy. The dose given at TPS was 200 cGy but after using MLC the dose was received because MLC protects healthy organs around the irradiation field. If the dose given is still within the range of -5 % and +7 %, it is still acceptable. The amount of radiation dose that can be reduced by using MLC in this study was 1,35 % for brain cases and 0,12 % for Glioblastoma cases.